HISTORY OF UZHHOROD ACCORDING TO ARCHAEOLOGICAL SOURCES: THE RESULTS OF STUDY - Пеняк, Павло (Modern engineering and innovative technologies, 2024)
The article deals with the results of the archaeological study of the ancient history of Uzhhorod. It belongs to the settlements of a special type, which existed for millennia before growing into a medieval city as an administrative and political center,